Beyond human rights : the legal status of the individual in international law - Peters, Anne, 1964- (2016)
"The starting point for this study is the observation that with increasing frequency, international legal norms directly address and engage individuals. For instance, individual rights under international law appear to arise from extradition treaties, treaties of friendship and establishment, double taxation agreements, transport treaties, intellectual property treaties, investment protection treaties, treaties on the legal status of foreigners, and the Vienna Convention on Consular Relations. On the side of duties, the criminal responsibility of individuals under international law has in recent decades been fleshed out by the work of the ad hoc criminal tribunals and the International Criminal Court"--
Definition of the question -- Historical thory and practice of the International legal status of the individual -- The doctrine of the International legal personality of the human being -- International individual obligations -- The International responsibility of the individual -- Individual rights arising from International responsibility -- Individual rights and duties in the law of armed conflict -- Protection against acts of violence and forces of nature -- The International legal status of victims of crime -- Rights and duties in investment protection law -- Individual rights in consular law -- Individual rights in diplomatic protection -- The legal basis for the interantional legal personality of the individual and the question of its independence from the state -- Human rights and other rights -- The individualized enforcement of international law -- Direct effect of norms establishing individual rights and duties -- The international individual right.
Previously published in German by Mohr Siebeck, 2014.
Includes bibliographical references (pages 556-590) and index.
Keywords: Human rights; Civil rights; Persons (International law); International law and human rights; Personality (Law); LAW -- International; Civil rights; Human rights; Individualrecht; Individuum; 2; Rechtsstellung; 2; Internationales Recht